Economics of Sissoo-rice Based Agroforestry System under Different Levels of Pruning - Nayak, H.; Koshta, L. D.; Bhol, N. (Indian Forester, 2014)
Sissoo-rice based agroforestry system is a economically viable system provided it is properly managed. Pruning of tree canopy is required to increase the economic return. Keeping this in view, the economic study of one such system was carried out at Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (India) during 2010. The sissoo trees were subjected to different levels of pruning (0, 25, 50 and 75% intensity) and three rice varieties (IR-36, MR-219 and WGL-32100) were grown with sissoo including in open condition. Irrespective of rice varieties, higher net monetary return was recorded -1 -1 -1 in sissoo 50% pruning + rice crop (` 40311 ha ) followed by 75% pruning ( 40186 ha ), 25% pruning ( 36517 ha ) and -1 lowest in no pruning + paddy (` 25859 ha ). Irrespective of pruning intensity, MR-219 recorded significantly higher -1 -1 monetary return (` 38715 ha ) closely followed by IR-36 (` 38363 ha ). WGL-32100 recorded the lowest net monetary -1 return (`30675 ha ).